Nanocompósitos de fosfato de cálcio com óxido de titânio síntese e caracterizações - Barbosa, José Hundemberg Pereira (2012)
Calcium phosphate ceramics have been investigated due their properties such as absence of toxicity and biocompatibility, enabling their use in medicine field being applied as a substitute for bone implants. However, other characteristics are required such as bioaffinity, mechanical and chemical resistances. Due to the difficulty of obtaining such properties in the pure phosphates, composites were proposed by combining the mechanical and physical properties of bio inert materials to the biological properties of bioceramics. In this work, nanocomposites of calcium phosphates and titanium oxide were synthesized, by the controlled hydrolysis of titanium tetrabutoxide in compositions between 1 and 10% in aqueous solutions of calcium chloride and ammonium phosphate. The solids were characterized by X-ray diffraction, infrared spectroscopy, thermogravimetric analysis and scanning electron microscopy. The results showed the incorporation of titanium oxide onto phosphate surface without loss of crystallinity and morphological changes. Evaluation of chemical stability of the nanocomposites showed that they were resistant to dissolution at pH below 6.0. The bioactivity tests showed that the nanocomposite containing 2% of titanium oxide was performed better than others